Lightweight Design Strategy and Performance Optimization of Spaceborne Core Network - Xi CHEN; Yiqun Zhao; Minghan ZHANG; Shan LU; Shihao WANG; Chengchen ZHANG; Xiaofan XU; Ping DU (天地一体化信息网络)
With the growth of global communication demand, the spaceborne core network can not only reduce frequent signaling interactions between satellites and the ground, but also break through the constraints of geographical regions, providing strong support for the integrated network architecture of heaven and earth and global communication operations.However, due to the resource limitations of satellites and the dynamic and time-varying topology of satellite internet on a large scale, the deployment of traditional core network elements in spaceborne environments has encountered significant challenges.This article is dedicated to studying the challenges of lightweight, flexible deployment, and low latency in onboard core networks, aiming to explore new design strategies for onboard lightweight core networks and provide a solid theoretical foundation for global communication operations.Multiple lightweight strategies, including minimum network element set deployment, single network element function tailoring, interface protocol lightweight, network element fusion and reconstruction, platform architecture lightweight, and transmission protocol reconstruction were firstly studied.Then, detailed simulation experiments were conducted on the selected strategies, and the experimental results confirmed that the lightweight processing of the spaceborne core network has superior performance in resource allocation and signaling process.